2016
DOI: 10.9734/bjmmr/2016/21446
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Predictors of Depression among Postpartum Mothers in the Limbe Health District, Cameroon: A Cross-Sectional Study

Abstract: Depression is a debilitating mood and mental disorder affecting approximately 13% of postpartum mothers worldwide with a prevalence of 25%-60% in low and middle income countries. The prevalence is yet to be published in Cameroon. Aim: This study was carried out to determine the prevalence, severity and risk factors of depression among postpartum mothers in Limbe Health District (LHD), Cameroon.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 20 publications
2
7
1
Order By: Relevance
“…Participants who experienced gender-based violence were more likely to be depressed. This is congruent with findings reported in the literature [8][9][10][11]. The occurrence of PPD was high in those with a family history of mental illness.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…Participants who experienced gender-based violence were more likely to be depressed. This is congruent with findings reported in the literature [8][9][10][11]. The occurrence of PPD was high in those with a family history of mental illness.…”
Section: Discussionsupporting
confidence: 92%
“…On the contrary, the prevalence of PPD in our study was lower than that reported by Ghogomu et al, in Limbe Cameroon (61.8%) [9]. This disparity could be explained by the fact that his study was community-based and assessed mothers up to 12 months postpartum there by exposing the mothers to other risk factors of depression other than childbirth.…”
Section: Discussioncontrasting
confidence: 92%
See 3 more Smart Citations